Asymmetric Total Synthesis of (−)‐Dehydrocostus Lactone by Domino Metathesis. Issue 25 (1st July 2021) - Kaden, Felix; Nowotni, Susanne; Höfner, Franziska; Lorenz, Melanie; Barthel, André; Jäger, Anne; Hennersdorf, Felix; Weigand, Jan J.; Metz, Peter
Abstract: An efficient total synthesis of the sesquiterpenoid (−)‐dehydrocostus lactone is reported. Our earlier approach by a domino enediyne metathesis was extended by a domino dienyne metathesis strategy to give access to suitably functionalized hydroazulene cores. Highly stereoselective asymmetric anti aldol reactions provided the enantiopure substrates for this key step of our synthesis. Multiple hydroboration/oxidation of the resulting hydroazulenes set up three out of four stereogenic centers in a single step. First, oxidation to give a diketo‐γ‐lactone enabled an enantioselective formal synthesis of the target guaianolide. Subsequently, the final steps of this approach were improved by using a double carbonyl olefination at the stage of a masked γ‐butyrolactone, which completed the synthesis in a much more efficient way. Abstract : Domino metathesis of the acyclic substrates 2 and 3 prepared by asymmetric anti aldol reactions gave access to suitably functionalized carbobicyclic cores of (−)‐dehydrocostus lactone (1 ). Subsequent transformation of these hydroazulenes to triol 4 by multiple hydroboration/oxidation installed three out of four stereogenic centers of the target sesquiterpenoid 1 in a single step and paved the way for lactonization. Late‐stage double carbonyl olefination in good yield was finally achieved after masking the γ‐lactone as an acetal.